Dengue Vaccines in a Changing Epidemiological Landscape: Current Evidence, Unresolved Challenges, and Public Health Considerations - Susanna Esposito; Nicola Principi (Vaccines, 2026)
Background: Dengue has expanded rapidly beyond traditional tropical and subtropical regions, driven by climate change, urbanization, population mobility, and the spread of competent Aedes vectors. Vaccination is an increasingly important component of dengue prevention, but development has been complicated by four viral serotypes, antibody-dependent enhancement, variable baseline serostatus, and the need for balanced and durable tetravalent immunity. Methods: We conducted a narrative review of PubMed/MEDLINE, Google Scholar, ClinicalTrials.gov, and relevant public health and regulatory sources. Evidence on dengue epidemiology, immunopathogenesis, licensed vaccines, advanced candidates, efficacy, immunogenicity, safety, durability, and implementation was critically evaluated. Priority was given to randomized trials, long-term follow-up studies, regulatory assessments, and surveillance data. Evidence was synthesized descriptively without formal meta-analysis or risk-of-bias assessment. Results: CYD-TDV was the first licensed dengue vaccine but is restricted to individuals with documented previous infection because seronegative recipients may experience an increased risk of severe dengue. TAK-003 has demonstrated overall efficacy against virologically confirmed dengue and dengue-related hospitalization in both baseline-seropositive and baseline-seronegative populations. However, protection is heterogeneous by serotype, and evidence remains limited or uncertain for some serotype-by-serostatus strata. Butantan-DV offers a promising single-dose strategy, but broader use requires additional long-term safety, effectiveness, and serotype-specific data. Inactivated, DNA, viral-vectored, virus-like particle, and mRNA vaccines remain investigational. Conclusions: Dengue vaccination should be integrated with surveillance, vector control, clinical preparedness, and risk communication. Population-based vaccination is most appropriate in high-transmission settings, whereas selective, risk-based strategies are preferable in temperate regions. Continued pharmacovigilance and effectiveness monitoring are essential to guide safe and equitable implementation.